Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas XI MAN 1 Kota Tasikmalaya (Studi Quasi Eksperimen Pada Mata Pelajaran Ekonomi Kelas XI IPS MAN 1 Kota Tasikmalaya Tahun ajaran 2023/2024) - Mega Yuliyanti; Rendra Gumilar; Raden Roro Suci Nurdianti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of the research is to determine the effect of the type Two Stay Two Stray type cooperative learning model on student learning outcomes in the economics subject class XI IPS MAN 1 Tasikmalaya city. This research uses quantitative methods with quasi-experimental designs. The population in this study was the entire class XI IPS MAN 1 Tasikmalaya city, totaling 192 students, the research sample was class XI IPS 1 as the experimental class and class The data collection technique used was by conducting a Pretest and Posttest which consisted of 25 questions with alternative multiple choice answers. The research results were seen from changes in Pretest and Posttest scores. In the experimental class which used the Two Stay Two Stray learning model, the results of the paired sample t-test obtained a significance value of 0.000 which was less than 0.05 and an N-Gain value of 0.44 which was interpreted as moderate. In the control class which uses the conventional model, the results of the paired sample t-test get a significance value of 0.000 which is smaller than 0.05 and the N-Gain value of 0.30 is interpreted as moderate.